Alih Kode dan Campur Kode dalam Lingkungan Komunikasi Mahasiswa Fakultas Bahasa dan Seni : (Analisis Bahasa Melalui Studi Sosiolinguistik) - Dwinda Khoyriyah; Berkatiah Berkatiah; Adellya Rosari Siregar; Yuliana Sari (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to describe and analyze the phenomenon of code switching and code mixing used by speakers in the Faculty of Languages ​​and Arts (FBS). This research is a qualitative descriptive research. The subjects used in this research were students and students in the Faculty of Languages ​​and Arts (FBS). The object of this research is speech about the use of code switching and code mixing used in everyday communication. The data collection techniques used in this research are direct observation, interviews and recording techniques. The results of this research show that the code switching and code mixing that occurred was Javanese, Batak, English and Indonesian. The types of code switching found were Indonesian to Batak, from Indonesian to Javanese, and from Indonesian to English and vice versa. The types of code mixing found are code mixing in and code mixing out using Indonesian, English and Javanese with word forms and expressions.